2016
DOI: 10.1088/1538-3873/129/971/015003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Infrared Sky Background for a High-Arctic Mountain Observatory

Abstract: Nighttime zenith sky spectral brightness in the 3.3 − 20 µm wavelength region is reported for an observatory site nearby Eureka, on Ellesmere Island in the Canadian High Arctic. Measurements derive from an automated Fourier-transform spectrograph which operated continuously there over three consecutive winters. During that time the median through the most transparent portion of the Q window was 460 Jy arcsec −2 , falling below 32 Jy arcsec −2 in N band, and to sub-Jansky levels by M and shortwards; reaching on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The Amundsen-Scott South Pole station's astronomical science activities have obtained a series of achievements. It found that the infrared sky emission was lower than typically found at mid-latitude sites in 1-2 orders of magnitude [1][2][3][4] and the atmosphere held extremely low precipitable water vapor [5]. The expectation of weak free-atmosphere turbulence was also confirmed.…”
Section: Introductionmentioning
confidence: 70%
“…The Amundsen-Scott South Pole station's astronomical science activities have obtained a series of achievements. It found that the infrared sky emission was lower than typically found at mid-latitude sites in 1-2 orders of magnitude [1][2][3][4] and the atmosphere held extremely low precipitable water vapor [5]. The expectation of weak free-atmosphere turbulence was also confirmed.…”
Section: Introductionmentioning
confidence: 70%
“…Several methods have been developed to estimate an off-axis PSF; and in principle these could be turned around to derive an on-axis PSF from off-axis stars. Typically, they require knowledge of the C 2 N distribution through the atmosphere [13,4] or observations of calibration frames containing many stars [19]. But it is also possible to make a reasonable (and sufficient) approximation to the way the PSF varies across a wider field using the science data alone, as long as at least one or two stars or compact objects are detected [5,6].…”
Section: Methods To Estimate the Psfmentioning
confidence: 99%